(untitled) - Carey, Francis A. (New York, 2006)
This book gives students a solid understanding of organic chemistry by stressing how fundamental reaction mechanisms function and how reactions occur. With the addition of handwritten solutions, new cutting-edge molecular illustrations, updated spectroscopy coverage, seamless integration of molecular modeling exercises, and state-of-the-art multimedia tools, the 6th edition of Organic Chemistry clearly offers the most up-to-date approach to the study of organic chemistry.
Anh Văn chuyên ngành Sư phạm Hóa
Keywords: Chemistry, Organic.,Hóa hữu cơ